BUDAYA KEARIFAN LOKAL PADA CERITA RAKYAT ISLAMI SEBAGAI BAHAN AJAR BAHASA INDONESIA (Local Wisdom Culture in Islamic Folklore as An Indonesian Language Teaching Material) - Muhlis Fajar Wicaksana; Titik Sudiatmi (SAWERIGADING, 2021)
AbstractThis study aims to develop the prototype of Indonesian language teaching material for the aspect of speaking skills by adopting the local culture and determine the level of stakeholder acceptance of the developed teaching material. This study was conducted using a research and development approach. The research samples were gathered using a purposive sampling technique. The data were obtained through the following stages: a focus group discussion (FGD) on the prototype of teaching material, evaluation of the prototype by expert judgment, limited and large-scale tryouts; and the stakeholder acceptance of teaching material. Data analysis was performed using a t-test by comparing the outcomes of learning using the developed learning material and the outcomes of learning using the provided material (compulsory book). The results of this study have depicted that the outcomes of teaching material prototype development are evaluated in terms of content feasibility, presentation feasibility, and linguistic feasibility. Evaluation on the stakeholder acceptance has revealed that the developed teaching material in the form of a calendar appears to be more effective than the teaching material in the form of a compulsory book. A calendar increases students’ interest and comfort while also teaching them to be more self-directed in their learning. AbstrakPenelitian ini bertujuan untuk mengembangkan prototipe bahan ajar bahasa Indonesia (aspek keterampilan berbicara) dengan mengadopsi budaya lokal dan untuk mengetahui keberterimaan stakeholders atas bahan ajar hasil pengembangan. Metode penelitian melalui pendekatan penelitian dan pengembangan. Teknik penarikan sampel menggunakan teknik purposive sampling. Teknik pengumpulan data melalui beberapa tahapan, yaitu focus group discussion (FGD) protipe bahan ajar, evaluasi prototipe oleh expertjudgement, uji coba terbatas dan uji coba lebih luas, keberterimaan stakeholders bahan ajar. Teknik analisis data melalui uji t-test dengan membandingkan hasil pembelajaran melalui produk hasil pengembangan dengan produk yang sudah digunakan (buku paket). Hasil penelitian menunjukkan, bahwa hasil pengembangan prototipe bahan ajar berupa aspek kelayakan isi, kelayakan penyajian, dan kelayakan kebahasaan. Keberterimaan stakeholders menunjukkan bahan ajar berbentuk kalender lebih efektif (produk hasil pengembangan) dibandingkan dengan bahan ajar yang berbentuk buku paket. Bahan ajar kalender membawa siswa lebih tertarik, lebih nyaman, dan melatih siswa untuk mandiri.